KILLING THROUGH DEATH: AN EMPIRICAL STUDY ON THE DRIVERS OF MODERN SUICIDE TERRORISM - García Beneito, Leopoldo (Journal of Terrorism Studies, 2025)
Departing from the idea that suicide attacks are a special form of terrorism, this article aims to shed light on some of its characteristics and particular dynamics to help better understand the phenomenon and effectively combat it. To that end, the article begins by exploring the trend of both types of terrorism, suicide and non-suicide, for after reviewing the main theories and findings on the topic by the academia in the literature review section. Following this overview, four variables are identified as potential drivers of suicide terrorism: inequality, foreign intervention, political freedom, and Islamic faith. The expected relationship between these variables and suicide terrorism conforms the hypotheses of the work. In a nutshell, a positive relationship is expected for all of them, except for the political regime, for which a negative relationship is predicted. By means of a logistic regression with a binary outcome model and data from the Global Terrorism Database between 2010 and 2020 (a total of 97,987 attacks), the analysis confirms all the hypotheses. The article ends by applying these findings to recent regional trends to explain the variations, and by issuing some policy recommendations that will help fighting the phenomenon.